Diffuse large B-cell lymphoma with continuously elevated immunoglobulin M following treatment: a case report with pathologic, immunophenotypic, and molecular analyses - Xiao, Fei; Cai, Yong-Mei; Fang, Jian-Chen; Shen, Yan-Ying; Yu, Bao-Hua; Zhang, Yi-Wei; Zhu, Di; Li, Zi-Hua; Li, Guo-Qing; Hou, Jian; Zhang, Min-Yue; Huang, Hong-Hui (Frontiers in Genetics, 2023)
A rare subtype of diffuse large-B cell lymphoma (DLBCL) has been reported to be accompanied by elevated immunoglobulin M (IgM) paraprotein in serum at diagnosis, called as IgMs-DLBCL. The monoclonal IgM paraprotein disappears soon after treatment in most of these patients. Here, we described a DLBCL patient with continuously elevated IgM following therapy. A 59-year-old male was diagnosed as DLBCL (GCB subtype per Hans algorithm, stage IA) with involvement of right cervical lymph node. After six cycles of immuno-chemotherapy with R-CHOP regimen, complete metabolic remission was achieved, but elevated level of serum IgM persisted.To investigate the origin of elevated IgM, pathologic, immunophenotypic, and molecular analysis of lymph node and bone marrow (BM) samples were performed preand post-treatment. BM infiltration of lymphoplasmacytic cells, and typical immunophenotypic profile by flow cytometry supported the diagnosis of Waldenström macroglobulinaemia (WM). MCD subtype of DLBCL was identified by next generation sequencing of lymph node at initial diagnosis characterized by co-occurring point mutations in MYD88 L265P and CD79B. Additionally, two different dominant clonotypes of immunoglobulin heavy chain (IGH) were detected in lymph node and BM by IGH sequencing, which was IGHV 3-11*06/IGHJ 3*02 and IGHV 3-11*06/IGHJ 6*02 respectively, speculating to be two independent clonal origin. This study will provide a panoramic understanding of the origin or biological characteristics of DLBCL co-occurring with WM.